METALS IN THE RIVER WATERS OF PRIMORYE - Shulkin V.M.; Bogdanov N.N.; Kiselev V.I. (My University, 2007)
New data are presented on the contents of Fe, Mn, Zn, Cu, Pb, Cd, and Ni in dissolved and particulate modes of occurrence in unpolluted or anthropogenically contaminated major rivers of Primorye. The background contents of dissolved metals are as follows: 0.1–0.5 g/l for Zn and Ni, 0.3–0.7 g/l for Cu, 0.01–0.04 g/l for Pb and Cd, and 2–20 g/l for Fe and Mn. Common anthropogenic loading (communal wastewaters) notably increases the dissolved Fe and Mn concentrations Industrial wastes lead to a local increase in the contents of dissolved metals in river waters by one to three orders of magnitude. The effect of hydrological regime is expressed most clearly in the areas of anthropogenic impact. The metal contents in the particulate matter are controlled mainly by its granulometric composition.